Large-scale survey reveals pervasiveness and potential function of endogenous geminiviral sequences in plants. Issue 2 (21st September 2020) - Sharma, Vikas; Lefeuvre, Pierre; Roumagnac, Philippe; Filloux, Denis; Teycheney, Pierre-Yves; Martin, Darren P; Maumus, Florian
Abstract: The family Geminiviridae contains viruses with single-stranded DNA genomes that have been found infecting a wide variety of angiosperm species. The discovery within the last 25 years of endogenous geminivirus-like (EGV) elements within the nuclear genomes of several angiosperms has raised questions relating to the pervasiveness of EGVs and their impacts on host biology. Only a few EGVs have currently been characterized and it remains unclear whether any of these have influenced, or are currently influencing, the evolutionary fitness of their hosts. We therefore undertook a large-scale search for evidence of EGVs within 134 genome and 797 transcriptome sequences of green plant species. We detected homologues of geminivirus replication-associated protein (Rep) genes in forty-two angiosperm species, including two monocots, thirty-nine dicots, and one ANITA-grade basal angiosperm species ( Amborella trichopoda ). While EGVs were present in the members of many different plant orders, they were particularly common within the large and diverse order, Ericales, with the highest copy numbers of EGVs being found in two varieties of tea plant ( Camellia sinensis ). Phylogenetic and clustering analyses revealed multiple highly divergent previously unknown geminivirus Rep lineages, two of which occur in C.sinensis alone. We find that some of the Camellia EGVs are likely transcriptionally active, sometimes co-transcribed with the same host genes across several Camellia species. Overall, our analyses expand the known breadths of both geminivirus diversity and geminivirus host ranges, and strengthens support for the hypothesis that EGVs impact the biology of their hosts.